Pleomorphic Adenoma of the Parotid: Extracapsular Dissection Compared with Superficial Parotidectomy—A 10-Year Retrospective Cohort Study. (21st October 2014) - Cristofaro, Maria Giulia; Allegra, Eugenia; Giudice, Amerigo; Colangeli, Walter; Caruso, Davide; Barca, Ida; Giudice, Mario
Abstract : The purpose of this study was to investigate the complication rates and effectiveness of extracapsular dissection compared with superficial parotidectomy for pleomorphic adenomas of the parotid gland from 2002 to 2012. The authors carried out a retrospective cohort study of 198 patients with pleomorphic adenomas of the parotid gland. Extracapsular dissection (ED) or superficial parotidectomy (SP) was performed. The recurrence rate and complications of the two surgical techniques were measured with a univariate analysis of each variable using the appropriate statistical analysis (chi-squared test or t- test). A total of 198 patients were enrolled between January 2003 and December 2012. The study included 97 females (48.99%) and 101 males (51.01%) whose mean age was 50.97 years (range 14–75). The type of surgery performed was ED in 153 patients (77.27%, 80 males and 73 females) and SP in 45 patients (22.73%, 21 males and 24 females). The mean follow-up time was 61.02 +/− 4.9 months for the patients treated with ED and 66.4 +/− 4.5 months for the patients treated with SP. Transient facial nerve injury and facial paralysis were significantly more frequent after SP than after ED (P = 0.001 and P = 0 . 065, resp.). No significant differences in capsular rupture, recurrence, and salivary fistula were observed after SP or ED: 2.2% versus 3.9%, 2.2% versus 3.3%, and 2.2% versus 0.65%, respectively. Extracapsular dissection may be considered the treatment of choice for pleomorphic adenomas located in the superficial portion of the parotid gland because this technique showed similar effectiveness and fewer side effects than superficial parotidectomy.